2018
DOI: 10.1186/s13567-018-0571-5
|View full text |Cite|
|
Sign up to set email alerts
|

Annexin A2 binds to vimentin and contributes to porcine reproductive and respiratory syndrome virus multiplication

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is an important globally distributed and highly contagious pathogen that has restricted cell tropism in vivo and in vitro. In the present study, we found that annexin A2 (ANXA2) is upregulated expressed in porcine alveolar macrophages infected with PRRSV. Additionally, PRRSV replication was significantly suppressed after reducing ANXA2 expression in Marc-145 cells using siRNA. Bioinformatics analysis indicated that ANXA2 may be relevant to vimentin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Vimentin is an important cytoskeletal protein involved in many virus infections. Interaction of annexin A2 with vimentin has been reported to enhanced virus replication in porcine reproductive and respiratory‐syndrome virus and porcine cicovirus type 2 . Furthermore, it has been demonstrated by Co‐IP, confocal laser microscopy, and bioinformatics that vimentin interacts with B domain of annexin A2 to enhance porcine reproductive and respiratory syndrome viral growth …”
Section: Association Of Annexin A2 With Other Virus Interacting Proteinsmentioning
confidence: 99%
“…Vimentin is an important cytoskeletal protein involved in many virus infections. Interaction of annexin A2 with vimentin has been reported to enhanced virus replication in porcine reproductive and respiratory‐syndrome virus and porcine cicovirus type 2 . Furthermore, it has been demonstrated by Co‐IP, confocal laser microscopy, and bioinformatics that vimentin interacts with B domain of annexin A2 to enhance porcine reproductive and respiratory syndrome viral growth …”
Section: Association Of Annexin A2 With Other Virus Interacting Proteinsmentioning
confidence: 99%
“…Virus titers were determined according to a previous report [32]. Briefly, MARC-145 cells, grown in 96-well plates, were infected with ten-fold serial dilution of samples.…”
Section: Virus Titrationmentioning
confidence: 99%
“…It was reported that vimentin was important for Epstein-Barr Virus LMP1-mediated Akt and ERK activation and transformation of rodent fibroblasts [30]. Cellular vimentin is also a specific host binding partner for 2C of FMDV [31], and Vimentin rearrangement plays a structural role in anchoring DENV2 to replication sites [32], and in facilitating efficient viral RNA replication with NS4A Protein [33], and in enhancing PRRSV growth by interacting with ANXA2 [34]. These results suggested that vimentin as intermediate filament in MDCK cells should be an important intracellular molecule for H9N2 virus entry and replication.…”
Section: Discussionmentioning
confidence: 99%